2016
DOI: 10.1080/13880209.2016.1211713
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-based metabolic study reveals the improvements of bitter melon (Momordica charantia) on energy metabolism in diet-induced obese mouse

Abstract: Context: Obesity can be ameliorated by some natural products such as polyphenol, flavones and saponin. As a typical medicinal plant, Momordica charantia L. (Cucurbitaceae) (bitter melon, BM) contains these natural chemicals and reduces diet-induced obesity in mice.Objective: This study evaluates the metabolic effects of dietary BM supplement, investigates a global metabolic profile and determines associated perturbations in metabolic pathways. Materials and methods: Male C57BL/6 mice were fed with low-fat diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It has good sources of catechin, gallic acid, chlorogenic acid [7] and saponin compounds [8], but also essential amino acids, vitamin C, vitamin A, carotenoids, folic acid, thiamine, riboflavin, niacin and minerals such as calcium, potassium, magnesium and sodium [2]. Indeed, body weight gain and blood sugar levels could be reduced as well as levels of energy metabolism could be increased in mice fed the powder-rich diet of Momordica charantia [9]. Furthermore, the oil from the seeds of M. charantia may regenerate tissue without side effects in healing rabbit skin [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has good sources of catechin, gallic acid, chlorogenic acid [7] and saponin compounds [8], but also essential amino acids, vitamin C, vitamin A, carotenoids, folic acid, thiamine, riboflavin, niacin and minerals such as calcium, potassium, magnesium and sodium [2]. Indeed, body weight gain and blood sugar levels could be reduced as well as levels of energy metabolism could be increased in mice fed the powder-rich diet of Momordica charantia [9]. Furthermore, the oil from the seeds of M. charantia may regenerate tissue without side effects in healing rabbit skin [10].…”
Section: Introductionmentioning
confidence: 99%
“…They found that this plant was antiobesogenic, and had the ability to modulate lipid proliferation, decrease body weight gain, visceral tissue weight, plasma and lipid concentrations, and lipid peroxidation in metabolism. The weight loss may be related to the increased energy of the rats, demonstrating that a diet rich in M. charantia extracts may aid in the treatment of obesity (Bian et al, 2016).…”
Section: Obesity Reductionmentioning
confidence: 99%